¿Riesgo de confusión o riesgo de complicación? - Barreda, Gonzalo (2023)
The article will be a critique of our trademark legislation, which, in pursuit of consumer protection that is practically nonexistent, disregards the wishes of trademark holders, thereby generating unnecessary litigation and costs for all parties, including the Authority itself. The current legislation obligates the Authority to reject ex officio the registration of trademarks that are considered, at the discretion of the Authority, to be confusingly similar to previously registered marks, even when the holder of the “protected” mark does not believe that the requested mark infringes on their rights. This is problematic because, first of all, it generates unnecessary negative consequences. For example, it forces parties to initiate lawsuits that they do not want, it affects investments because trademarks are registered to be used, so an unnecessarily rejected mark implies a delay in the entry of a business into the market, or it generates disinterest in the entrepreneur who was going to enter the Peruvian market, and it prevents alternative forms of conflict resolution, such as arbitration, from being considered. Secondly, the purpose that would justify such negative consequences, consumer protection, is not achieved in reality because, for example, the rejected mark can still exist in the market, authorized by the holder of the registered mark (the mark on the basis of which the Authority ex officio rejected the registration of the mark).